DESAIN PENGEMBANGAN BUKU AJAR BAHASA ARAB BERBASIS PENDIDIKAN KARAKTER DAN BUDAYA KELAS A DAN B TK ISLAM - Zukhaira, Zukhaira; Hasyim, Mohamad Yusuf. A. (Jurnal Penelitian Pendidikan, 2013)
This study aims to know the development of the Arabic language textbook based character education in kindergarten Islam Gunungpati Semarang district, know the results and effectiveness of the development of the Arabic language textbook based character education in kindergarten Islam Gunungpati Semarang District. This research uses research development with the development of research procedures according to Borg and Gall From the research presented, some conclusions can be taken as follows: 1) Competency Standards, Basic Competency and indicators of achievement of competence which made researchers have adapted to thematic material contained in Government Regulation No. 58 of 2009 on Early Childhood Education Standards and adjusted to the decision of the Minister of National Education of Character-based Education and Culture. 2) The expert appraisal 18:33% excellent, 56.67% good, and 25% fair, and 3) the effectiveness of the textbook can be seen from the tests that have been done in TK A and B.